The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-1694027
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and the Military Male

Abstract: Male infertility is a condition that affects approximately 50% of infertile couples and about 30% of those couples have only male factor infertility identified. There has been speculation that male military service members may have an even greater lifetime prevalence of infertility as compared to the general population, but very few scientific publications focus on male factor infertility in the military population specifically. This review will discuss many of the unique considerations regarding male infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Other authors studying the Mexican army population found a high prevalence of seminal HPV in healthy soldiers (49%) and concluded that a risky sexual behavior, a large number of sexual partners, and anal intercourse increase the risk of acquiring and transmitting an STI [ 19 ]. Additionally, the military status contributes to the development of several psychological, endocrinological, and immunological alterations due to stress, as reported in military communities [ 7 , 20 ]. Such conditions can increase the susceptibility to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors studying the Mexican army population found a high prevalence of seminal HPV in healthy soldiers (49%) and concluded that a risky sexual behavior, a large number of sexual partners, and anal intercourse increase the risk of acquiring and transmitting an STI [ 19 ]. Additionally, the military status contributes to the development of several psychological, endocrinological, and immunological alterations due to stress, as reported in military communities [ 7 , 20 ]. Such conditions can increase the susceptibility to infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are other risk factors such as risky sexual behavior, a large number of sexual partners and anal intercourse, which increase the risk of acquiring and transmitting an STI, including HPV infection in males [ 27 ]. Additionally, military status contributes to the development of psychological, endocrinological and immunological alterations due to stress [ 28 , 29 ]. Such conditions can increase the susceptibility to chronic HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“…'sexy soldiers' [15,18,58,59], whereas others have argued that the costs of fighting decrease the reproductive success of fighters relative to non-combatants, e.g. 'worn-out warriors' [18,[60][61][62]. Rather than arbitrarily choosing a position on this argument, the probability of each individual reproducing in our model (i.e.…”
Section: (Ii) Distribution Of Benefits (Reproductions)mentioning
confidence: 99%